Tindakan Genosida Terhadap Etnis Rohingnya Dalam Perspektif Hukum Pidana Internasional - Fikroh Ainiyah; Efa kusmalasari (Hakim: Jurnal Ilmu Hukum dan Sosial, 2024)
the actions taken by the Myanmar Government against its Rohing ethnic groups have fulfilled the element that this action can be categorized as a crime of genocide. The requirement for an action can be said to be an act of genocide, if it has fulfilled elements such as mass murder, carried out systematically, discriminated against a religion, and aimed at eliminating a certain minority ethnic or group. Therefore, the actions taken by the Myanmar government have fulfilled the above elements, so it can be concluded that the actions taken by the Myanmar government against the Muslim Rohing ethnicity are international genocide crimes. Keywords: Genocide, International Criminal Law, Rohingya. Rohingya community has experienced various forms of human rights violations that include genocide crimes, especially since 1978. The right to freedom of movement for the spirits is tightly restricted and the issuance of the Citizenship Law Act which resulted in Myanmar freely discriminating against people who are not has a citizenship status. The issues raised in this study are the actions undertaken by Myanmar is a crime of genocide, as well as efforts to resolve disputes between Myanmar and ethnic spirits. This type of research uses the type of normative legal research that is by literature studies and literature related to genocide, and using historical approaches, statutory approaches, concept approaches and case approaches. The results of this study indicate that the actions taken by Myanmar to the spirits of the Muslim community are indeed a genocide crime, based on some elements in accordance with Article 6 of the Rome Statute 1998. The Dispute Resolution is litigated, as non- litigation settlements can not find the bright spot of the dispute, and who handles the case is the International Criminal Court with the ICC tribunal. The conclusion is that Myanmar has committed genocide crimes against its ethnic spirits and discrimination against minorities. Furthermore, the efforts of dispute settlement are conducted by litigation or through legal mechanism and handled by ICC (International Criminal Court).